Visual Field Testing with Head-Mounted Perimeter ‘imo’ - Matsumoto, Chota; Yamao, Sayaka; Nomoto, Hiroki; Takada, Sonoko; Okuyama, Sachiko; Kimura, Shinji; Yamanaka, Kenzo; Aihara, Makoto; Shimomura, Yoshikazu (PloS one, 2016)
We developed a new portable head-mounted perimeter, "imo", which performs visual field (VF) testing under flexible conditions without a dark room. Besides the monocular eye test, imo can present a test target randomly to either eye without occlusion (a binocular random single eye test). The performance of imo was evaluated. Using full HD transmissive LCD and high intensity LED backlights, imo can display a test target under the same test conditions as the Humphrey Field Analyzer (HFA). The monocular and binocular random single eye tests by imo and the HFA test were performed on 40 eyes of 20 subjects with glaucoma. VF sensitivity results by the monocular and binocular random single eye tests were compared, and these test results were further compared to those by the HFA. The subjects were asked whether they noticed which eye was being tested during the test. The mean sensitivity (MS) obtained with the HFA highly correlated with the MS by the imo monocular test (R: r = 0.96, L: r = 0.94, P < 0.001) and the binocular random single eye test (R: r = 0.97, L: r = 0.98, P < 0.001). The MS values by the monocular and binocular random single eye tests also highly correlated (R: r = 0.96, L: r = 0.95, P < 0.001). No subject could detect which eye was being tested during the examination. The perimeter imo can obtain VF sensitivity highly compatible to that by the standard automated perimeter. The binocular random single eye test provides a non-occlusion test condition without the examinee being aware of the tested eye.